IUS VENDENDI OF THE PLEDGEE AND THE ISSUE OF THE RESPONSIBILITY FOR EVICTION IN ROMAN LAW - Sič, Magdolna I; Milutin, Milan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
In this paper we are discussing the following issues: the development of the right to sell (ius vendendi) the pledge by the pledgee in case of pignus; the question of the basis of the pledgee’s right to transfer the ownership onto the buyer as a non-owner, contrary to the ‘nemo plus iuris’ rule; and related to these, the question of the responsibility for eviction. Our main research question is, who will be responsible for the eviction of the pledged thing from the buyer – the creditor or directly the debtor? This question was very topical in ancient Rome. A significant number of sources evidence that pledging other peoples’ things was frequent practice. This was enabled by the fact that land records as well as records of other things served primarily to secure tax collection, they were not accurate and were seldom available to private individuals. Following the casuistic solutions of classical jurists based on the bona fidei principle, we can find an answer to our question in the Justinian law: the debtor is directly responsible for the eviction of the sold pledge – an answer that is, in our opinion, also acceptable in the contemporary law.